A espiritualidade e o processo analítico: um olhar - Vasconcellos, Walkiria Santos (2005)
This dissertation presents the spirituality issue present or not in patients during the analytical process, from the study of spirituality history and of some theory of the psychoanalysis development, having as purpose analysing the presence or not of spirituality in patients and its link with the psychic development levels. In order that an approach of psychoanalysis with spirituality might occur the spirituality history has been in part raised and an study about the human psychic development has been performed using theorical propositions of Winnicott, Klein and Bion showing through theorical pieces of each author, how each of them understands the spirituality issue. In accordance with such theorical research the spirituality is being considered as the human being capacity of providing sense to his existence and of having a God inside, understood as a good object internally kept. The final considerations show throught the clinical cases brought, that spirituality is a result of a psychic state evolution